2009
DOI: 10.1111/j.1365-2125.2009.03531.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate prescribing in an Irish elderly population in primary care

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Potentially inappropriate prescribing in older people is a well‐documented problem and has been associated with adverse drug reactions and hospitalization.• Beers' criteria, Screening Tool of Older Persons' potentially inappropriate Prescriptions (STOPP) and Screening Tool to Alert doctors to Right Treatment (START) are screening tools that have been formulated to help physicians and pharmacists identify potentially inappropriate prescribing and potential prescribing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

46
256
12
19

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(334 citation statements)
references
References 40 publications
(49 reference statements)
46
256
12
19
Order By: Relevance
“…7,8 However, prescribing 'appropriately' in multimorbidity is not always straightforward. 9,10 Guidelines exist for most common chronic diseases and offer benefits associated with the best available evidence, but adhering to guidelines in the management of a patient with multimorbidity almost invariably leads to multiple medications, resulting in increased risk of drug interactions, adverse effects, and poor adherence. 11,12 Furthermore, most guidelines do not consider patient preferences, quality of life, or the expected time to benefit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 However, prescribing 'appropriately' in multimorbidity is not always straightforward. 9,10 Guidelines exist for most common chronic diseases and offer benefits associated with the best available evidence, but adhering to guidelines in the management of a patient with multimorbidity almost invariably leads to multiple medications, resulting in increased risk of drug interactions, adverse effects, and poor adherence. 11,12 Furthermore, most guidelines do not consider patient preferences, quality of life, or the expected time to benefit.…”
Section: Introductionmentioning
confidence: 99%
“…14,36 Implications for research and practice Although GPs in this study provided logical reasons for their decisions, the potential negative outcomes associated with both polypharmacy and suboptimal disease management must be remembered and ways to support GPs' prescribing in multimorbidity are thus required. 9 In hospital specialties, there is an increasing trend towards multidisciplinary team (MDT) meetings, which operationalise collaborative decision making to deliver evidence-based yet patient-centred care. The potential for multidisciplinary review in primary care has been evaluated in trials such as PINCER, a pharmacist-led information technology intervention that reduced medication errors in general practice.…”
mentioning
confidence: 99%
“…7 To quantify potential inappropriate prescribing (IP) in older people, Beers' criteria were found to be most widely cited in the literature. 3 We explored the appropriateness of use of medicines for older patients from the perspectives of healthcare professionals and patients using Beers' criteria to quantify Potentially Inappropriate Medicines (PIM).…”
Section: Introductionmentioning
confidence: 99%
“…30 Studies have showed that PPI use is associated with malabsorption of vitamins and 31 minerals 7,8 , an increased risk of infections, such as pneumonia 9 and enteric infection 10 , and 32 an increased fracture risk 11,12 . These potential side effects can be minimized through 33 appropriate prescription practices in terms of stepping down the dose or stopping long-term 34 treatment altogether. 35 As a consequence of this dramatic increase in PPI use and the associated potential risks, 36 clinical guidelines in the UK have recommended rationing the use of the PPI in the primary 37 care setting, either by stepping down the dose or stopping treatment all together 13 .…”
mentioning
confidence: 99%